Konsepsi Ruang Urban Yogyakarta dalam Kurasi Festival Film Dokumenter dan Jogja-NETPAC Asian Film Festival 2019 - Setiawati, Sri Ratna (Sekolah Pascasarjana Institut Kesenian Jakarta, 2019)
The non-government film festival post-1998 held every year as part of festival ecosystem in Yogyakarta. This research examined on Festival Film Dokumenter (FFD) and Jogja-NETPAC Asian Film Festival (JAFF) in 2019. Both festival have taking place for more than a decade and was organised by young people, mostly student. The research examining the Yogyakarta’s urban space conception inside FFD dan JAFF 2019, by using the production of space theory by Henri Lefebvre (1991) and the heterotopia theory by Michel Foucault (1984). It examined through the urban theme in the festival program, which has been the foundation for both festival in producing their social spaces. The research method used the qualitative method with data collecting via the participation observation, interview, field note and literature study. Both film festival has established the ideal construction of Yogyakarta, however at the same time they were resistant against the mainstream media and the commercial films distribution-exhibition domination, until they succeeded in developing the power to become the new hegemony of the Indonesian film industry.Festival film non-pemerintah yang lahir pasca-1998 berlangsung setiap tahun, menjadi bagian dari ekosistem festival di Yogyakarta. Penelitian ini dilakukan terhadap Festival Film Dokumenter (FFD) dan Jogja-NETPAC Asian Film Festival (JAFF) pada tahun 2019. Kedua festival telah berlangsung selama lebih dari satu dasawarsa dan digerakkan oleh anak muda yang mayoritas adalah mahasiswa. Penelitian bermaksud menelaah konsepsi ruang urban Yogyakarta di dalam penyelenggaraan FFD dan JAFF 2019, dengan menggunakan teori produksi ruang Henri Lefebvre (1991) dan heterotopia Michel Foucault (1984), melalui tema urban dalam festival programming, yang menjadi dasar bagi kedua festival memproduksi ruang sosialnya. Penelitian ini menggunakan metode kualitatif dengan pengumpulan data melalui pendekatan pengamatan terlibat, wawancara, pembuatan catatan lapangan, dan studi pustaka. Hasil penelitian ini menemukan bahwa kedua festival film membangun konstruksi Yogyakarta ideal namun pada saat yang sama juga melakukan perlawanan terhadap dominasi media mainstream dan distribusi-ekshibisi film komersial, sehingga berhasil membangun kekuatan untuk menjadi hegemoni baru perfilman Indonesia.